TENDENCIES OF CHANGE IN VISUAL ART EDUCATION - Paulionytė, Jûratë (Acta Paedagogica Vilnensia, 2007)
The purpose of this theoretical study is to explore contemporary directions of visual art education. The theme is analyzed with the purpose to investigate ant evaluate peculiarities of visual art education in accordance with new technologies. The work summarizes theories and conceptions in this area.Some aspects of impact of new technologies on visual art and creative process were analyzed. Digital technologies help students overcome temporal and spatial limitations and expand their domain of activities. Its impact on creative process is great. Key peculiarities characterizing creative process and imagery are technology competence, virtual reality, integration and interactivity. Virtual reality presents new possibilities which can be created only in such a digital way. For young people this virtual space is attractive very much and they are under the impression that digital imagery can’t be replaced.Computer is a new tool for design creations. But visual art education should not be restricted to teaching students how to use all the range of technical devices. What is much more important is to teach them how to handle media aesthetics. Contemporary dimensions of visual art education are not only aesthetics, technology competence, synthesis of different art but also traditional goals of developing creativity, artistic talent and self – identity. Cultural and historical context dimensions of visual art education aren’t new but digital space expanded their ranges. Visual art teacher’s role in art classes is changing from knowledge provider to adviser and assistant.Two tendencies are discussed in the article. The first tendency is the belief that visual art education must radically alter its course. Such course correction is believed necessary if the young people are to be prepared to live effectively in a culture that is increasingly reliant on aggressive visual imagery. The second tendency states that studying visual culture is complicated because it goes beyond the goals of developing creativity, artistic talent and aesthetic experience. The analysis revealed that the new fundamental solutions are required in education. Common competencies such as visual, social, communication etc. should be teaching at the schools and universities. Then, every school discipline can contribute its different special content for teaching of competencies.
Keywords: visual art education; contemporary visual art technologies; visual literacy; visual culture